German law on circumcision and its debate: How an ethical and legal issue turned political. (23rd December 2013) - Aurenque, Diana; Wiesing, Urban
Abstract The article aims to illuminate the recent debate in Germany about the legitimacy of circumcision for religious reasons. The aim is both to evaluate the new German law allowing religious circumcision, and to outline the resulting conflict between the surrounding ethical and legal issues. We first elucidate the diversity of legal and medical views on religious circumcision in Germany. Next we examine to what extent invasive and irreversible physical interventions on infant boys unable to given their consent should be carried out for non‐medical reasons. To this end, the potential benefits and harms of circumcision for non‐medical reasons are compared. We argue that circumcision does not provide any benefits for the 'child as a child' and poses only risks to boys. We then set out to clarify and analyse political (rather than ethical) justifications of the new circumcision law. We demonstrate through this analysis how the circumcision debate in Germany has been transformed from a legal and ethical problem into a political issue, due at least in part to Germany's unique historical context. Although such a particular political sensibility is entirely comprehensible, it raises particular problems when it comes to framing and responding to medical ethical issues – as in the case of religious circumcision.